ANALISIS KINERJA ROUTING PROTOKOL SPRAY AND WAIT DI JARINGAN OPPORTUNISTIC - Maria Irmgrad Ratu; Bambang Soelistijanto (Fakultas Teknologi Informasi Universitas Kristen Satya Wacana, 2017)
Opportunistic Network (OppNet) is a wireless network that doesn’t need any infrastructure in the formation.Opportunistic Network can not guarantee a path between the source and destination at any time. In this research, the authors tested the Epidemic Routing Protocols and Spray And Wait Routing Protocol using ONEsimulator. Performance metrics used are Delivery Probability, Overhead Ratio, Average Latency, Buffer Occupancy and Number of Drop messages. Parameters used in each test is the area that remains with the addition of the number of nodes, increasing the buffer size, the addition of the Time-To-Live (TTL), increasing the number of copies of the message (L Copy), and the increase in the number of nodes and the number of copies (%).Epidemic Routing Protocols Tests showed an increase on the Delivery Latency Average Probability, it’s because Epidemic Routing Protocol always leave copy of messages every time they met with a relay node without regard to resources. While Spray and Wait Routing Protocols is good at it because Overhead Ratio in Spray and Wait is low because of number of copies limitation. But delay in Spray and Wait s very high compared to the Epidemic, it is because Spray And Wait limits the number of copies. From the simulation that involved buffersize addition. Delivery probability in epidemic routing protocol reached an optimum number of 95%, meanwhile delivery probability in SnW protocol reached 73.24%, thus, in every 100 messages sent, 73 messages are successfully delivered.